The Management of odontogenic focal infections of cerebral abscess patient under local anesthesia - Cita Dharmastuti; Bambang Dwiraharjo; Elisabeth Riyati Titi Astuti (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2017)
Cerebral abscess is a localized suppurated infection in between of a brain tissue caused by a wide variety of bacteria, fungi, and protozoa. The etiology of cerebral abscess includes chronic suppurated disease, congenital cardiomyopathy, or a trauma from a neurosurgical procedure. Sinusitis, otitis, and untreated odontogenic infections promote the formation of a brain abscess. The purpose of this case report was to present the management of an odontogenic focal infection in a case of cerebral abscess. Thirty six years old male referred to the Policlinic of Oral Surgery of Dr. Sarjito Central General Hospital, Yogyakarta by the Neurology Department to investigate the focal infection in the oral cavity of the patient with a cerebral abscess. The patient was treated on the Neurology Department for six month with initial complaint of headache, seizures, nausea, vomiting, and unable to move his right extremity. After a drug therapy, complaints were gradually receded. Based on the anamneses and clinical examination, an abnormality on the other organ was not suspected, but two impacted teeth and several radices were found in the oral cavity. Focal infection elimination was performed twice under a local anesthesia. Four weeks after the treatment, the neurological complaint of patient was decreased. The management of odontogenic cerebral abscess required a collaboration of the neurologist, radiologist, neurosurgeon, and oral surgeon. The treatment was aimed to eliminate the focal infection and reduce the effects caused by the mass of necrotic tissue, suppurated inflammatory response and edema on the surrounding cerebral tissue